Effect of fluoride gels supplemented with sodium trimetaphosphate in reducing demineralization - Danelon, Marcelle [UNESP]; Takeshita, Eliana Mitsue [UNESP]; Peixoto, Ligia Carla [UNESP]; Sassaki, Kikue Takebayashi [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP] (Springer, 2014)
The objective of this study was to evaluate the in vitro effect of low-fluoride (F) gels supplemented with sodium trimetaphosphate (TMP) on enamel demineralization.Bovine enamel blocks (n = 160) were selected based on surface hardness (SH) and divided into eight treatment groups (n = 20 per group): no F or TMP (placebo), 3 % TMP (3 %TMP), 5 % TMP (5 %TMP), 4,500 mu g F/g (4,500), 4,500 mu g F/g + 3 % TMP (4,500 3 %TMP), 4,500 mu g F/g + 5 % TMP (4,500 5 %TMP), 9,000 mu g F/g (9,000), and 12,300 mu g F/g (acid gel). Blocks were subjected to demineralization/remineralization cycling for 5 days. Subsequently, surface hardness (SH1) and integrated loss of subsurface hardness (Delta KHN) were assessed, and the concentrations of loosely bound (CaF2-like) and firmly bound (FA-like) formed and retained F were determined.The 4,500 5 %TMP and acid gel groups showed similar results and had the lowest mineral loss (SH1 and a dagger KHN). The acid gel group had the highest concentration of CaF2-like F, but the formation and retention of FA-like F was greater in the 4,500 5 %TMP group than in the acid gel group (p < 0.05).It is possible to inhibit enamel demineralization with low-F gels supplementing these gels with 5 % TMP.The low-F gel containing TMP can be regarded as a safer alternative for clinical use from a toxicological point of view since it contains half of the amount of a conventional formulation while promoting similar anticaries effect.
Keywords: Demineralization; Fluoride; Gels; Phosphates